Activating Methanol for Chemoselective Transfer Hydrogenation of Chalcones Using an SNS-Ruthenium Complex - Mohar, Kailash; Phukan, Hirak Jyoti; Mondal, Avijit; Soni, Kaushik; Srimani, Dipankar (Synlett, 2024)
Methanol is gaining popularity as a transfer-hydrogenating agent in catalytic reduction reactions because of its bulk-scale production and inexpensive nature. Current research interests include the utilization of methanol as a safe and sustainable hydrogen source for chemical synthesis and drug development. In particular, the chemoselective reduction of α,β-unsaturated ketones is of great interest because of their prevalence in many natural products. We investigated the potential application of acridine-derived SNS-Ru pincer complexes in methanol activation for chemoselective reduction of chalcones. Our developed catalytic system showed broad substrate tolerance, including substrates containing reducible functional groups. Control experiments and postsynthetic applications are also highlighted.
Keywords: ligands; ruthenium catalysis; methanol activation; chalcones; reduction; chemoselectivity